Strengthening capacities for the scaling of Local Technical Agroclimatic Committees through collaborative action - Castellanos, Andrea Estefania; Martinez Baron, Deissy (2025)
The Climate Action Platform in Agriculture for Latin America and the Caribbean (PLACA) prioritized Local Technical Agroclimatic Committees (LTACs, MTAs in Spanish) in their 2024 action plan as a strategic mechanism to enhance climate resilience and sustainability in agriculture. MTAs enhance climate resilience in Latin American agriculture by improving decision-making and adaptation strategies. PLACA, the Alliance of Bioversity International and CIAT, and WMO supported implementing MTA action plans through capacity-building workshops, enabling new countries to advance in actions to implement MTAs, while others strengthened their expertise.